Gender and social inclusion impact of climate change, COVID shocks and stresses on agriculture and food systems in Tanzania: The case of Maasai women in Chalinze district - Genda, Elizabeth Lulu (Mzumbe University, 2023)
Consideration to gender matters is important for the equity of climate change adaptation programs and effective food security. The overlaying global socioecological emergencies of climate change and the COVID-19 pandemic have simultaneously impacted food security. The study assessed the impacts of climate change and COVID-19 outbreak on food security among Maasai using gender lenses. The paper is a result of mixed-methods research design that mainly relied on interviews, focus group discussion, and questionnaire. The findings shows that Maasai women were facing difficulties caused by climate change long before COVID-19 outbreak due to their nomadic nature, where men migrated with livestock to areas with better pasture and water for livestock— leaving behind women and children. This affected women because they depend on milk and its products for family consumption and income; consequently, absence of livestock triggered food insecurity. The study recommended that government and its agencies and stakeholders: increase their consideration to the climate change stresses on agriculture and food systems through gender programs; strengthen the integration of research into climate adaptation programs; increase advocacy for coping with climate change–related risks in relationship to nature and ecosystems and values that drive inequalities in development and resist social reforms.